2018
DOI: 10.1016/j.envpol.2018.03.081
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the impacts of acid and nitrogen additions on carbon fluxes in European conifer and broadleaf forests

Abstract: Increased reactive nitrogen (N) loadings to terrestrial ecosystems are believed to have positive effects on ecosystem carbon (C) sequestration. Global "hot spots" of N deposition are often associated with currently or formerly high deposition of sulphur (S); C fluxes in these regions might therefore not be responding solely to N loading, and could be undergoing transient change as S inputs change. In a four-year, two-forest stand (mature Norway spruce and European beech) replicated field experiment involving a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 33 publications
(9 citation statements)
references
References 65 publications
1
8
0
Order By: Relevance
“…Our results highlight the importance of forest type on net ecosystem N retention, consistent with previous studies that demonstrated species‐specific effects on N cycling (Booth et al, 2005; Oulehle et al, 2018; Templer et al, 2005). The ∼45% greater biomass N increment (Table 3) in West Bear hardwood compared to East Bear hardwood stands suggests N additions reduced N limitations resulting in accelerated biomass and N annual increment in the treated watershed.…”
Section: Discussionsupporting
confidence: 92%
“…Our results highlight the importance of forest type on net ecosystem N retention, consistent with previous studies that demonstrated species‐specific effects on N cycling (Booth et al, 2005; Oulehle et al, 2018; Templer et al, 2005). The ∼45% greater biomass N increment (Table 3) in West Bear hardwood compared to East Bear hardwood stands suggests N additions reduced N limitations resulting in accelerated biomass and N annual increment in the treated watershed.…”
Section: Discussionsupporting
confidence: 92%
“…Organic functional groups associated with the much higher organic matter concentration and content in North Buck than South Buck also provided a greater capacity in North Buck to buffer against decreased acidity of soil solutions (Ross et al, ) as acidic deposition rates decreased. This interpretation is supported by a recent experiment that showed a more stressed microbial community in acidic soil of a Norway spruce stand than in soil of a less acidic beech stand at the start of the experiment, an effect that was intensified with the addition of sulfuric acid (Oulehle et al, ).…”
Section: Discussionmentioning
confidence: 61%
“…Second, the nutrient limitation of microbial growth due to soil base cation loss (e.g. Mg 2+ , Ca 2+ ) (Bowman et al 2008, Oulehle et al 2018) and other ion (e.g. H + , Al 3+ ) toxicity (Tian and Niu 2015) tend to reduce soil heterotrophic respiration.…”
Section: Discussionmentioning
confidence: 99%